Gamifikasi dalam Pengajaran Bahasa Inggris dengan Menggunakan Platform Genially - Sibghatullah Mujadidi; Siti Suharsih; Putri Intan Oktapiani; Isyarah Khaeraini; Nur Addiena Kamila; Nabila Mutiara Fajris (Jurnal Pendidikan dan Sastra Inggris, 2023)
Genially is one of the educational tools that advocates interactive visual communication. Genially serves as a comprehensive online platform where teachers can create captivating presentations, interactive graphics, infographics, gamification, quizzes, breakouts, portfolios, and more, enriching them with interactivity and animation effects within seconds. The objective of this workshop's research is to identify students' perceptions of the impact of the gamification teaching method using the Genially platform and to engage and enhance students' interest in the field of education through ELT (English Language Teaching). In this study, various findings related to the respondents' views on the gamification approach in teaching English using the Genially platform were discovered. The results indicate that the gamification approach through the Genially platform receives a positive response from participants regarding the English learning process, particularly including students' interest and motivation in learning English. This research is expected to serve as innovation, inspiration, and evaluation for educators and students in its implementation within English language teaching and learning through gamification methods using the Genially platform, involving various other instruments in the future.